ANALISA KEKUATAN KONSTRUKSI BRACKET TOWING HOOK PADA TB. BONTANG DENGAN METODE ELEMEN HINGGA DAN RULES BKI - Mulyatno, Imam Pujo; Arswendo A, Berlian; Alan, Muhammad (Department of Naval Architecture - Diponegoro University, 2012)
Bracket towing hook construction planning is to make a construction that has the stress level of the allowable limit and can be accepted by the construction. Requirements for towing hook are structural strength if the stress levels that occur below the elastic region. By calculating the value of the maximum load, maximum stress, von mises stress and deflection (displasment) that occur in the construction of bracket towing hook, so that known security level of construction that has been designed. Research on construction of the strength bracket towing hook need to be considered and carried out, where the stress caused by load about them should not exceed the maximum limit Ïƒyield materials and Ïƒallow based on the rules from the class. The reference to rules used in this research is based on the rules of Bureau Classification Indonesia. Analysis of the strength bracket towing hook construction is done by using finite element methode. The analysis used is a static load analysis to determine the characteristics and location of greatest stress on the construction bracket towing hook based on three variations of loading. Analysis results obtained using finite element methode based program of greatest stress maximum occurs in the condition of the bracket towing hook Â with maximum horse power load that is equal to 44,2 N/mm2 where the most critical area occurs at node 457 which is located at frame number 23 lengthwise section and stiffener number 7 cross section. This stress is still in a safe condition because after compared with material Ïƒyield of 400 N/mm2 and Ïƒallow based BKI rules of 178,12 N/mm2 produce safety factor value of 9,05 and 4,03